Synthesis and characterization of gold nanoparticles doped zinc oxide nanostructures for ultraviolet photodetector application - Omar Hamad Ahmed, 1983-, author 639366 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2021)
Thesis (Doktor Falsafah (Fizik)) - Universiti Teknologi Malaysia, 2021